Characterization of Group 10‐Metal‐p‐Substituted Phenoxyl Radical Complexes with Schiff Base Ligands. Issue 31 (6th November 2017) - Oshita, Hiromi; Kikuchi, Misa; Mieda, Kaoru; Ogura, Takashi; Yoshimura, Takayoshi; Tani, Fumito; Yajima, Tatsuo; Abe, Hitoshi; Mori, Seiji; Shimazaki, Yuichi
Abstract: Methylthiophenoxyl radical plays an important role as the active form of galactose oxidase (GO), which catalyzes oxidation of a primary alcohol to the corresponding aldehyde. Although many metal(II)‐phenoxyl radical species have been reported, only a few studies have been reported on the properties of methylthiophenoxyl radical‐metal complexes. We have prepared the group 10 metal (Ni, Pd and Pt) complexes of a salen‐type ligand with a methylthio group at para ‐position of the two phenolate moieties and characterized them by X‐ray crystal structure analyses and various spectroscopic methods in order to understand the role of the methylthio moiety in phenoxyl radical metal complexes. The corresponding p ‐methoxy substituted derivatives have been also characterized for comparison. All the one‐electron oxidized group 10 metal methylthiophenolate complexes have a relatively localized radical site on one of the two phenolate moieties in comparison to the one‐electron oxidized complexes of p ‐methoxy derivatives and exhibit different properties dependent on the central metal ions. Abstract : Sulfur atom binding phenoxyl radical plays an important role in the active forms of galactose oxidase. In order to understand the nature of the metal binding MeS‐phenoxyl radical, we investigated the detailed geometric and electronic structures of one‐electron oxidized MeS substituted bis(phenoxide)‐group 10 metal complexes of Schiff base ligands and clarified the diffferences from the properties of the MeO substituted complexes by various physicochemical methods.